The interconnection of the loads in the planning of the training, in the sport of boxing - Lázaro Alberto Pastor Chirino; Lázaro de la Paz Arencibia; María de Lourdes Rodríguez Pérez (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
The present work is framed in the context of the alternatives related to the planning of the sport training, from the ATR models (accumulation-transformation-realization). In correspondence with the conceptions used today in training planning, the importance of the interconnection of the contents in the preparation of boxers is evident, from the conjugation of loads whose metabolic routes are fundamentally phosphagenic, alactic anaerobic and lactic anaerobic glycolithic. The objective of the research is to assess the situation of the training planning, based on the most current trends related to the interconnection of the loads and the ATR model in the preparation of the boxers of the Provincial Academy of Pinar del Río. For the study it was selected a sample, consisting on 13 athletes and 7 coaches from the Provincial Boxing Academy of Pinar del Río. Different methods and techniques such as the interview, the observation and the measurement were used. This study was carried outin correspondence with the most advanced conceptions regarding training planning. It reveals the importance of the interconnection of the contents in the preparation of the boxers from the combination of lactic anaerobic loads and lactic ones. However, the documents and guidelines of the National Boxing Commission still do not meet all the expectations of the pedagogical groups of trainers of the academy, which leaves a margin for interpretation by the Technical Commissions of the territories as regards alternatives, the planning of training and the definition of the directions and interconnection of these. It is necessary to find a mechanism that, at the didactic level, better orients the trainer in this sense.